SOTAKOKEMUSTEN HYÖDYNTÄMINEN MERIVOIMIEN OPERAATIOTAIDON JA TAKTIIKAN KEHITTÄMISESSÄ - Säämänen, Juuso (Suomen Sotatieteellinen Seura - The Finnish Society of Military Science, 2012)
Because of the general situation during the Continuation War, open sea warfare was emphasized in the development of naval tactics whereas the coastal artillery concentrated on the development of firing methods. These developments were based on the observations of the tactics used by the Soviet Navy and Marines as well as the lessons learned in the tests and exercises carried out by friendly forces. The observations and lessons learned were related to the troops in reports named “Naval and Coastal War Experiences” and “Fleet War Experiences”. During the war also Germans helped in the developing of Finnish naval tactics. The German Naval Attache to Finland, Rear Admiral Reimar von Bonin, suggested that Finnish naval officers be ordered to visit Germany in November 1941. The purpose of these visits was to teach the Finnish officers about the tactics of the German Navy as well as increase their combat experience. Von Bonin’s suggestion was motivated by the idea that the Finnish Navy’s area of operations might expand to the White and Arctic Seas. The visits of Finnish navy and coastal artillery officers started in the winter of 1942. Altogether dozens of Finnish officers as well as a few petty officers visited Germany in 1942–1944. As a result of these visits the Finns were able to develop, amongst other things, their motor torpedo boat and anti-submarine warfare tactics. They also gained valuable information about the operational principles of coastal troops and the countermeasures against influence mines. The tactical and technical lessons learned in Germany were still in use in the 1950’s. The collection of war experiences began in the Finnish Navy in October 1944, only a month after the war between Finland and the Soviet Union had ended. The collection was completed during the winter months of 1944–1945. The objective was to gather material for regulations and manuals. The collected material ...